The Importance of Child-Friendly Spaces for Children's Well-being - Ahmed, L .Omar Hama Ahmed; Maulud, L.Paewast Rahman; Ahmed, L. Abas Sharif Ahmed; Rahman, Asst.L. Zanyar Maqsud Rahman (Sulaimani Journal for Humanities, 2026)
Children are adversely affected by war and conflict, often getting displaced and forced to become refugees in very volatile conflict situations. They are compelled to evacuate their residences and relocate to areas that may lead to an unconventional setting for children, such as refugee camps. Child Friendly Spaces (CFSs (are facilities created by organizations and governments to prioritize the well-being of children during catastrophes. The objective of this study is to comprehend the importance of child-friendly settings, specifically focusing on the contribution of Social Workers(SWs) employed at CFSs in enhancing the welfare of children. The methodology approach used is qualitative descriptive research, which involves conducting many semi-structured interviews using three different formats: one-on-one, focus group, and mini group interviews. Interviews were done with: (Community Mobilizer; Facilitator and Social Workers) who have had or now have employment in the CFSs for a duration of one to several years, including different phases and diverse settings such as camps, schools, youth centers, and Juvenile Children Reformatory(JCR). The study's results indicate that Child Friendly Spaces play a crucial role in promoting the well-being and providing psychological support for children. SWs play a vital role in CFSs, since they bear significant role to identify children who have unresolved issues such as difficulty in interaction, lack of attention or curiosity, and lack of enjoyment in activities. The study findings have substantial implications for parents, policy makers, and educators about the role of CFSs and SW in emergency circumstances. However, it is essential to consider the viewpoint of children as well; Hence, more inquiry is required from this standpoint.
Keywords: Child friendly space childrens wellbeing psychosocial support Social worker